Child Protection in International Law: Synergy between CRC, Humanitarian Law, and Human Rights - Dahlial, Fauzi; Maulana, Ramza Fatria; Yunarti, Sri (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study examines child protection from the perspective of international law, focusing on the synergy between three principal instruments: the Convention on the Rights of the Child (CRC), International Humanitarian Law (IHL), and Human Rights (HR). Although each framework has distinct characteristics, they complement one another in ensuring the fulfillment and protection of children's rights, both in times of peace and during armed conflict. The CRC provides a comprehensive normative framework emphasizing the best interests of the child, whereas IHL specifically regulates the protection of children in the context of armed conflict, including the prohibition of child soldier recruitment and the safeguarding of education and safety rights. Meanwhile, human rights law serves as a universal foundation whose guarantees cannot be suspended, even in states of emergency. This research employs a normative-juridical method combined with a qualitative approach to examine the interrelation among these three legal systems and the challenges in their implementation. The analysis reveals that the main issues stem from the gap between international norms and their enforcement at the national level, including jurisdictional conflicts, weak law enforcement, and the lack of harmonization with domestic legislation. To address these challenges, integrative strategies are needed, including regulatory harmonization, capacity-building for state officials, strengthening cross-sectoral cooperation, and enhancing the role of civil society in monitoring mechanisms.